First report of cassava common mosaic disease and Cassava Common Mosaic Virus infecting cassava (Manihot esculenta) in Peru - Fernandez Huaytalla, Elizabeth (2017)
Cassava common mosaic disease (CCMD) can cause root yield losses of approximately 30% (Venturini et al. 2016) in cassava (Manihot esculenta Crantz) and it has already been reported in Brazil, Colombia, Paraguay, and Argentina (Calvert et al. 2012; Di Feo et al. 2015). Most of Peru’s cassava production is in the eastern side of the country (the rainforest region) and is mainly used for direct human consumption. Cultivated area in these regions is approximately 48.1 thousand hectares (MINAGRI 2015). CCMD is caused by Cassava common mosaic virus (CsCMV; Calvert et al. 1996), a mechanically transmitted potexvirus that can be disseminated via infected stem cuttings used for cassava propagation. Given the presence of the disease in neighboring countries, a field survey for virus diseases in cassava was organized during June 2016 in the province of Huaral, in the central coast of Peru, where typical leaf mosaic and leaf deformation symptoms associated to CCMD were observed in local cassava varieties. To verify the presence of CsCMV and CCMD in Peru, the youngest leaves of four plants showing virus-like symptoms and four plants not showing symptoms were collected from one of the affected fields and dried in silica gel for analysis. Double antibody sandwich (DAS)-ELISA tests using a polyclonal antiserum readily detected CsCMV in all symptomatic samples (Nolt et al. 1991). In addition, mechanical transmissions to the experimental host Nicotiana benthamiana induced typical systemic leaf mosaic. RT-PCR tests targeting the replicase region of CsCMV were carried out using primers CsCMV-3269-F: 5′-GAGGCTCTTCTCTGGGAAAC-3′ and CsCMV-3896-R: 5′-CTTGAGTCCAGTTTGATGTC-3′, designed using an alignment of CsCMV-related sequences available in GenBank. An expected PCR fragment of 627 bp was obtained only in samples showing symptoms of CCMD. RT-PCR tests for other cassava-infecting viruses reported in the Americas (Carvajal-Yepes et al. 2014) were negative in these samples. PCR products from two independent CsCMV-positive samples were sent for direct Sanger-sequencing (Macrogen, Korea). CsCMV sequence isolates from Peru (GenBank accession nos. KX964625 and KX964626) show a nucleotide identity of 88 to 93%, and an amino acid sequence identity of 99% with other CsCMV sequences available in GenBank, and phylogenetic analysis clustered Peruvian isolates with CsCMV sequences reported in cassava. These results stress the need to implement surveillance activities and quick diagnostic protocols, as the inadvertent propagation and accumulation of virus infections could cause an increasingly negative effect on cassava and other vegetatively propagated crops.